The dilemma of teachers’ unfavorable working conditions and political ideology on the teaching history in Zimbabwe: selected cases - Chakawa, Joshua (2016)
Zimbabwean secondary school history teachers have taken their political inclinations and dire economic situation into the classroom. There is a deliberate attempt by ZANU-PF opponents to infuse their political ideologies to learners as they go about their teaching business. Equally the same, those supportive of the government and the ruling party sometimes take their line of thinking into the classroom. Further, certain topics in ‘O’ Level History Paper 1 and ‘A’ Level Paper 5 meant to be taught and in the syllabus are skipped and war veterans may not be welcome as resource persons. In addition, there is some kind of reluctance by instructors to openly discuss certain topics which are deemed sensitive because the teachers themselves are suspicious of each other. In addition, the meager salaries received by teachers have increased their potential of carrying their frustrations into the classroom. The research was a product of a survey that was carried out in some Zimbabwean schools with a bias towards Midlands Province. It sought to establish how poverty and political affiliation has affected the teaching of history and how that has ultimately impacted on the student. Use was made of chosen topics that teachers find sensitive when teaching. There was also an attempt to interview the bulk of ‘O’ Level and ‘A’ history teachers. The paper is crucial because it unpacks how the silent war in schools impact on concerned stakeholders inclusive of parents. It also unveils how the Zimbabwean government has used history to bolster its support. From 1980 to 2002, history was optional in schools and then made compulsory from 2003 with some papers thought to be aligned to the West being scrapped from the syllabus.